2006
DOI: 10.1073/pnas.0507367103
|View full text |Cite
|
Sign up to set email alerts
|

ATM promotes apoptosis and suppresses tumorigenesis in response to Myc

Abstract: Overexpression of the c-myc oncogene contributes to the development of a significant number of human cancers. In response to deregulated Myc activity, the p53 tumor suppressor is activated to promote apoptosis and inhibit tumor formation. Here we demonstrate that p53 induction in response to Myc overexpression requires the ataxia-telangiectasia mutated (ATM) kinase, a major regulator of the cellular response to DNA double-strand breaks. In a transgenic mouse model overexpressing Myc in squamous epithelial tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
116
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 58 publications
8
116
0
Order By: Relevance
“…The basis for the narrow tumor predisposition of Atmdeficient mice is unclear. Atm-null mice have only been reported to show increased susceptibility to lymphoid tumors and a modest increase in squamous cell tumors in a Myc transgenic model (42). Two possibilities are as follows: a unique role of Atm in lymphoid lineages or a specific lack of redundant pathways to Atm in lymphoid tissue, which would expose the vulnerability of Atm loss.…”
Section: Discussionmentioning
confidence: 99%
“…The basis for the narrow tumor predisposition of Atmdeficient mice is unclear. Atm-null mice have only been reported to show increased susceptibility to lymphoid tumors and a modest increase in squamous cell tumors in a Myc transgenic model (42). Two possibilities are as follows: a unique role of Atm in lymphoid lineages or a specific lack of redundant pathways to Atm in lymphoid tissue, which would expose the vulnerability of Atm loss.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the fractions of early lesions in such tissues will probably show higher frequency of DDR barrier activation than in the corresponding malignant lesions, similar to the data based on different stages of progression among human lung, bladder and colon tumours, for example (Gorgoulis et 2007). Second, cell culture and mouse model experiments in numerous laboratories demonstrated that activated oncogenes evoke a robust DDR activation in diverse cell types, including primary fibroblasts, lymphocytes and epithelial cells (Powers et al, 2004;Gorgoulis et al, 2005;Bartkova et al, 2005aBartkova et al, , 2006Di Micco et al, 2006;Frame et al, 2006;Pusapati et al, 2006;Reimann et al, 2007;.…”
Section: Dna Damage Response As a Candidate Tumorigenesis Barrier In mentioning
confidence: 99%
“…Oncogenic stress created by sustained Myc expression has been shown to induce DNA damage through a variety of mechanisms (29)(30)(31). The detection of DNA damage plays an important role in eliminating nascent tumors (27,28).…”
Section: E -Myc ͉ Innate Immunity ͉ Tumorigenesismentioning
confidence: 99%